From Waste to Golden Opportunity: A Portrait of Community's Social and Economic Transformation Through the Application of the 3R Concept in the Era of Sustainable Development - Arundina Dijah Retno Pratiwi; Fandi Ahmad; Lidia Maasir (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
This research is a qualitative research that presents an overview of the social and economic transformation that can be achieved through the application of the 3R (Reduce-Reuse-Recycle) concept in the Cipageran Community 22 Sukatani Village, West Java Regency.